Security comparison of ownCloud, Nextcloud, and Seafile in open source cloud storage solutions - Ibrahim, Md (My University, 2022)
Cloud storage has become one of the most efficient and economical ways to store data over the web. Although most organizations have adopted cloud storage, there are numerous privacy and security concerns about cloud storage and collaboration. Furthermore, adopting public cloud storage may be costly for many enterprises. An open-source cloud storage solution for cloud file sharing is a possible alternative in this instance. There is limited information on system architecture, security measures, and overall throughput consequences when selecting open-source cloud storage solutions despite widespread awareness. There are no comprehensive comparisons available to evaluate open-source cloud storage solutions (specifically owncloud, nextcloud, and seafile) and analyze the impact of platform selections. This thesis will present the concept of cloud storage, a comprehensive understanding of three popular open-source features, architecture, security features, vulnerabilities, and other angles in detail. The goal of the study is to conduct a comparison of these cloud solutions so that users may better understand the various open-source cloud storage solutions and make more knowledgeable selections. The author has focused on four attributes: features, architecture, security, and vulnerabilities of three cloud storage solutions ("ownCloud," "Nextcloud," and "Seafile") since most of the critical issues fall into one of these classifications. The findings show that, while the three services take slightly different approaches to confidentiality, integrity, and availability, they all achieve the same purpose. As a result of this research, the user will have a better understanding of the factors and will be able to make a more informed decision on cloud storage options.
Keywords: Cloud Storage, Cloud storage security, Features, Architecture, Vulnerability, Open source cloud storage, ownCloud, Nextcloud, Seafile